Decentralisation and Ethnic Politics: A Reflection of Two Decades of Indonesia’s Decentralisation - Mukrimin, Mukrimin (Universitas Negeri Semarang, 2018)
This article aims to examine what Indonesia has achieved in the last decades of decentralisation. In other words, has decentralisation brought about what its prominent advocators yearned for? How do “decentralisers”– supporters and prominent advocators of local autonomy - play their roles in re-actualising or reinventing their local identities? How has local identity emerged within the state’s territory? Empirically, most new splitting regions (pemekaran) (both province and district) are formed through mobilisation of etnhnic and religious sentiments. Specifically, ethnic politics continue to contribute to the development of the West Sulawesi. Decentralisation, at the changing political landscape, has been seen as a new opportunity and arena for local elites to compete against others to control the local governments.